Neurocommunication as a strategy to prevent suicide in young people - Leal Jiménez, Antonio (IROCAMM - International Review Of Communication And Marketing Mix, 2020)
Suicide is a complex phenomenon that has attracted attention throughout the times of humanity. Virtually all religions are coincident in their rejection as a means of ending one’s life. The common basis for this rejection is that it is God who gives life and He is the only one capable of taking it away. Carrying out this study is justified since it is a subject that draws attention worldwide due to the increase in the registration of cases, becoming a Public Health problem. Due to its severity it requires our attention, although unfortunately its prevention and control are not an easy task. With this work, we intend to know its scope at present in the young population and to what extent communication can be considered as a prevention tool using Artificial Intelligence and neurocommunication. It is carried out from an extensive bibliographic review and the performance of a qualitative exploratory study. There is a need to propose communication campaigns using new tools provided by neurosciences and Artificial Intelligence, through social networks. We have not found enough previous studies and their application to the object of study. It is, therefore, an approach that will need to be consolidated.